PENGARUH DAYA KREATIVITAS DAN PRESTASI BELAJAR TATA KECANTIKAN TERHADAP MINAT BERWIRAUSAHA PADA MAHASISWA AKS-AKK YOGYAKARTA - Harwiyati, Enny (Jurnal Socia Akademika, 2024)
This study aims to analyze the influence of creativity and cosmetology learning achievement on entrepreneurial interest in AKS – AKK Yogyakarta students. This study uses a quantitative approach with a correlational survey method. The population in this study is all students of the Cosmetology study program at AKS "AKK" Yogyakarta. The research sample was determined by proportional random sampling technique. The sample was taken from 30 final semester students who had taken the beauty course and had recorded learning achievements. The instrument used in this study is a questionnaire to measure creativity using a likert scale with creativity indicators including originality, flexibility, elaboration, and fluency and measure entrepreneurial interest with indicators such as the desire to open a business, business motivation, and business planning. The results of the research showed that creativity had a significant influence on students' entrepreneurial interest, with a probability value of 0.000 (< 0.05) and learning achievement did not show an important impact on entrepreneurial interest, with a probability value of 0.732 (> 0.05). These findings indicate that traditional academic success, such as test scores or GPA, is less relevant in encouraging students to be entrepreneurial. Non-academic factors such as soft skills, hands-on experience, and environmental support tend to play a bigger role